2003
DOI: 10.1103/physreve.68.015101
|View full text |Cite
|
Sign up to set email alerts
|

Topology of the world trade web

Abstract: Economy, and consequently trade, is a fundamental part of human social organization which, until now, has not been studied within the network modeling framework. Here we present the first, to the best of our knowledge, empirical characterization of the world trade web, that is, the network built upon the trade relationships between different countries in the world. This network displays the typical properties of complex networks, namely, scale-free degree distribution, the small-world property, a high clusteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
414
1
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 566 publications
(458 citation statements)
references
References 15 publications
15
414
1
10
Order By: Relevance
“…With respect to the distribution of the degree k (x) Garlaschelli & Loffredo (2004) claim that it is not a power law and therefore the WTW is not a scale-free network. On the other hand, they agree with Serrano & Boguñá (2003) in finding both disassortativity and that the clustering coefficient is decreasing in k, suggesting the presence of a hierarchical structure. Serrano et al (2006) build a weighted directed network of trade imbalances with links directed from net importers to net exporters.…”
Section: Papers In the Physics Domainsupporting
confidence: 84%
See 2 more Smart Citations
“…With respect to the distribution of the degree k (x) Garlaschelli & Loffredo (2004) claim that it is not a power law and therefore the WTW is not a scale-free network. On the other hand, they agree with Serrano & Boguñá (2003) in finding both disassortativity and that the clustering coefficient is decreasing in k, suggesting the presence of a hierarchical structure. Serrano et al (2006) build a weighted directed network of trade imbalances with links directed from net importers to net exporters.…”
Section: Papers In the Physics Domainsupporting
confidence: 84%
“…A number of recent papers has studied the topological properties of the International Trade Network (ITN), but has only relied on binary (unweighted) analysis (Serrano & Boguñá 2003, Garlaschelli & Loffredo 2004. This means that a link between any two countries in the network is either in place or not depending on whether the trade flow is greater than some given threshold.…”
Section: Motivations and Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] the proximity φ αβ of products α and β was introduced as the symmetrized probability that a country exports product α, given that it exports product β. (2) where C i is the set of products exported by country i, P(α ∈ C i |β ∈ C i ) is the probability of exporting product α given that β is being exported, and φ αβ is the proximity of α and β. The proximity Φ iα of product α to country i is defined as the average proximity of products in i's export basket to product α…”
Section: International Trade Metricsmentioning
confidence: 99%
“…The complex network approach was used in Ref. [2] and showed that the international trade exhibits common features with the World Wide Web network. It has been shown that many features of the international trade can be explained using models based on the gravity equation [3][4][5].…”
Section: Introductionmentioning
confidence: 99%